Tumor Apolipoprotein E is a key checkpoint blocking anti-tumor immunity in mouse melanoma - Wu, Xiaofang; Srinivasan, Priya; Basu, Mousumi; Zhang, Peng; Saruwatari, Michele; Thommandru, Bernice; Jacobi, Ashley; Behlke, Mark; Sandler, Anthony (Frontiers in Immunology, 2022)
Immunotherapy is a key modality in the treatment of cancer, but many tumors remain immune resistant. The classic mouse model of B16-F10 melanoma is immune resistant even in the face of checkpoint inhibition. Apolipoprotein E (apoE), a known immune suppressant is strikingly elevated in many human tumors, but its role in cancer immunology is not defined. We investigated the role of apoE in the immune micro-environment using a mouse melanoma model. We demonstrate that ApoE is -highly expressed in wild-type B16-F10 melanoma and serum levels progressively increase as tumors grow. The conditioned media from wild type ApoE secreting melanoma cells suppress T-cell activation in vitro while this suppressive effect is absent in conditioned media from ApoE knock out tumor cells. Mechanistically, apoE induces IL-10 secreting dendritic cells and stimulates T-cell apoptosis and arrest partially via the lrp8 receptor. Ablating ApoE in mice inoculated with tumor cells enabled tumor cell rejection and was associated with induction of immune pathway activation and immune cell infiltration. Tumor secreted apoE appears to be a potent immune cell checkpoint and targeting apoE is associated with enhanced tumor immunity in the mouse melanoma model.